2015
DOI: 10.1177/1933719115589414
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Metabolites Produced by Cytochrome P450 3A Modulate Uterine Contractility in a Murine Model

Abstract: We seek to characterize the effect of progesterone metabolites on spontaneous and oxytocin-induced uterine contractility. Study Design: Spontaneous contractility was studied in mouse uterine horns after treatment with progesterone, 2a-hydroxyprogesterone, 6b-hydroxyprogesterone (6b-OHP), 16a-hydroxyprogesterone (16a-OHP), or 17-hydroxyprogesterone caproate (17-OHPC) at 10 À9 to 10 À6 mol/L. Uterine horns were exposed to progestins (10 À6 mol/L), followed by increasing concentrations of oxytocin (1-100 nmol/L) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…While fetal clearance of progesterone is minute with respect to overall clearance, fetuses who express an active CYP3A5 were estimated to form ~3-times more 6β-OHP than nonexpressers. Based on our prior in vitro work indicating pro-contractility effects of 6β-OHP and anti-contractility effects of 16α-OHP (10), we hypothesize that the higher 6β-OHP/16α-OHP ratio in CYP3A5 expressers may contribute to increased preterm labor risk in CYP3A5 expressers. Additional studies are needed to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…While fetal clearance of progesterone is minute with respect to overall clearance, fetuses who express an active CYP3A5 were estimated to form ~3-times more 6β-OHP than nonexpressers. Based on our prior in vitro work indicating pro-contractility effects of 6β-OHP and anti-contractility effects of 16α-OHP (10), we hypothesize that the higher 6β-OHP/16α-OHP ratio in CYP3A5 expressers may contribute to increased preterm labor risk in CYP3A5 expressers. Additional studies are needed to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…(37, 38) We have recently reported that the primary metabolites of progesterone, 6β-OHP and 16α-OHP, have contradictory effects on oxytocin-induced contractile frequency. (10) While previous studies have shown that progesterone is metabolized in the liver by CYP3A enzymes, the relative importance of the three human isozymes CYP3A4, CYP3A5, and CYP3A7 had not been described. (12, 13, 39) Therefore, we undertook the current study to examine the CYP3A isozyme specific metabolic formation of 6β-OHP and 16α-OHP in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations